Arthroscopic Coracoclavicular Reconstruction Combined with Open Acromioclavicular Reconstruction Using Knot Hiding Clavicular Implants Is a Stable Solution - Juha O. Ranne, M.D., Ph.D; Severi O. Salonen, B.M; Terho U. Kainonen, M.D; Jussi A. Kosola, M.D., Ph.D; Lasse L. Lempainen, M.D., Ph.D; Mika T. Siitonen, M.Sc; Pekka T. Niemi, M.D., Ph.D (Elsevier, 2021)
Purpose: The purpose of this noninterventional, register-based study was to report the outcomes and wound healing of surgically treated chronic acromioclavicular (AC) dislocations using a tendon graft and knot-hiding titanium implants. Methods: Thirty-two cases with chronic AC separation underwent an arthroscopic coracoclavicular (CC) ligament reconstruction and an open AC ligament reconstruction using knot-hiding titanium implants. The wound healing was assessed 2 months after the operation. The Nottingham Clavicle score, Constant score, and Simple Shoulder Test were obtained postoperatively and at a minimum of one-year postsurgery. The radiographic change in distance between the clavicular and coracoid cortices and clavicular tunnel diameter was measured. General patient satisfaction with the outcome (poor, fair, good, or excellent) was also assessed 1 year postoperatively. Results: The mean Nottingham Clavicle score increased from a preoperative mean of 41.66 ± 9.86 to 96.831 ± 5.86 (P ≤ .05). The Constant score increased from a preoperative mean of 44.66 ± 12.54 to 93.59 ± 7.01 (P ≤ .05). The Simple Shoulder Test score increased from a preoperative mean of 7.00 ± 2.14 to 11.84 ± .63 (P ≤ .05). The coracoclavicular distance increased from 11.32 ± 3.71 to 13.48 ± 3.79 mm (P ≤ .05). The clavicular drill hole diameter increased from 6 mm to a mean of 6 to a mean of 8.13 ± 1.12 mm. Twenty-three (71.9%) patients reported an excellent outcome, and nine (28.1%) reported a good outcome. One clavicular fracture occurred but no coracoid fractures. There was one reconstruction failure leading to a reoperation. Conclusions: In this series, combining the arthroscopic CC ligament reconstruction to an open reconstruction of the AC joint with a tendon graft proved to be a stable solution. The knot-hiding titanium implant effectively eliminated the problems related to the clavicular wound healing. Level of Evidence: Level IV, therapeutic case series.